Hope in end-of-life cancer patients: A cross-sectional analysis. Issue 5 (October 2021) - Bovero, Andrea; Opezzo, Marta; Botto, Rossana; Gottardo, Francesco; Torta, Riccardo
Abstract: Objective: Hope promotes oncology patients' adaptability to their illness, regardless of the stage of cancer. This study aimed to determine the prevalence of hope in a sample of end-of-life patients and to investigate the possible relationships between hope and a set of clinical and psychosocial measures. Method: Three hundred and fifty end-of-life oncology patients, with a presumed life expectancy of 4 months or less and a Karnofsky Performance Status (KPS) of 50 or lower, were administered the Italian validated versions of a set of rating scales during their first consultation with a psychologist. This included the Herth Hope Index (HHI), Patient Dignity Inventory (PDI), Demoralization Scale (DS), Hospital Anxiety and Depression Scale (HADS), Functional Assessment of Chronic Illness Therapy (FACIT-Sp), and the Visual Analogue Scale for pain (VAS). Results: On average, the sample scored between moderate and high on the HHI and the average level of spirituality was high. However, most patients had clinically relevant anxious and depressive symptomatology and high levels of demoralization. Other than the pain scale, the total HHI score significantly correlated with the total scores of all rating scales and their subscales, as well as with the measure of personal religious practice. The "Meaning" FACIT-Sp subscale was found to be the main predictor of hope. Significance of results: Since hope represents a core need and a tool for patients dealing with their illness, it is essential to implement stage-specific and realistic hope-facilitating interventions and support patients in their search for meaning, which promotes spiritual well-being and appears relevant in fostering hope.